2017
DOI: 10.1016/j.abb.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of acetyl-CoA carboxylase 1 and senescence in human fibroblasts involves oxidant mediated p38 MAPK activation

Abstract: We sought to explore the fate of the fatty acid synthesis pathway in human fibroblasts exposed to DNA damaging agents capable of inducing senescence, a state of irreversible growth arrest. Induction of premature senescence by doxorubicin or hydrogen peroxide led to a decrease in protein and mRNA levels of acetyl-CoA carboxylase 1 (ACC1), the enzyme that catalyzes the rate-limiting step in fatty-acid biosynthesis. ACC1 decay accompanied the activation of the DNA damage response (DDR), and resulted in decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…This study unveils a role for FASN in controlling senescence establishment that contributes to explain the effect of FASN inhibitor, C75 27 . Importantly, C75 was reported to inhibit senescence in human diploid fibroblasts 21 , although it was unclear which senescent pathway was affected, whereas other reports show that C75 induce senescence in fibroblast 48 . Here we report that cellular senescence is inhibited in HSCs not only by treatment with C75 but also by FASN knockdown using a specific shRNA.…”
Section: Discussionmentioning
confidence: 98%
“…This study unveils a role for FASN in controlling senescence establishment that contributes to explain the effect of FASN inhibitor, C75 27 . Importantly, C75 was reported to inhibit senescence in human diploid fibroblasts 21 , although it was unclear which senescent pathway was affected, whereas other reports show that C75 induce senescence in fibroblast 48 . Here we report that cellular senescence is inhibited in HSCs not only by treatment with C75 but also by FASN knockdown using a specific shRNA.…”
Section: Discussionmentioning
confidence: 98%
“…10 Mavrogonatou et al 34 reported that there was a link between p38 MAPK pathway and oxidative stress, and both of them were involved in TNF-a-induced premature senescence of human dermal fibroblasts. Both oxidative stress and p38 MAPK pathway participated in metabolic perturbation-triggered senescence of human primary fibroblasts 35 and TNF-a-induced premature senescence of human dermal fibroblasts. 34 Suppression of p38 MAPK pathway could block the accumulation of ROS in senescent skin fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in addition to the activation of the DNA damage-response cascade of molecular events, DOX produces a prompt reduction in the levels of acetyl-CoA carboxylase 1, the enzyme that catalyzes the rate-limiting step in fatty acid synthesis. Such induction of synchronized inhibition of proliferation and anabolism by DOX was seen in pulmonary fibroblasts [ 94 ]. In a recent study, cardiac fibroblasts exposed to DOX prematurely acquired a senescent phenotype, too, as shown by the increases in SA- β -gal activity and the expression of senescence markers p16 INK4a and p21 [ 95 ].…”
Section: Cardiac Fibroblastsmentioning
confidence: 99%